A Primary Adrenal Epithelioid Angiomyolipoma (PEComa) in a Patient with Tuberous Sclerosis Complex: Report of a Case and Review of the Literature - Nancy Torres Luna; Jorge Esteban Mosquera; Isin Yagmur Comba; Mustafa Kinaan; Jorge Otoya (Case Reports in Medicine)
Epithelioid angiomyolipomas (EAMLs) are mesenchymal tumors that are part of the family of the perivascular epithelioid cell neoplasms (PEComas). These tumors portray a potential aggressive behavior with metastatic lesions found in around 30% of reported cases. EAMLs might present sporadically or in association with the tuberous sclerosis complex (TSC). They typically involve the kidneys, liver, and lungs. It is extremely rare for these tumors to arise from other organs. The present report describes an unusual case of an adult patient with a history of TSC who developed EAML of the adrenal gland. Moreover, he presented with metastatic disease to the liver, a feature rarely described. The diagnosis of EAMLs can be challenging as they are hard to distinguish from other adrenal or renal tumors without a thorough histopathologic and immunohistochemical evaluation. Due to the potential aggressive behavior of these malignancies, timely diagnosis is extremely important and has significant therapeutic and prognostic implications.